ANALISIS PENGARUH CELEBRITY ENTREPRENEUR DAN ELECTRONIC WORD OF MOUTH (E-WOM) TERHADAP PURCHASE DECISION DENGAN BRAND AWARENESS SEBAGAI VARIABEL MEDIASI: STUDI KASUS PADA STREET BOBA DI SEMARANG - Alif Sap Aisyi; Sri Rahayu Tri Astuti (Faculty of Economics and Business Diponegoro University, 2022)
Celebrities are now not only known as entertainers but also as endorsers and even entrepreneurs. The rise of businesses built by celebrities makes it easier for brands to be known, because celebrity involvement is stronger so that they are considered as communicators who have a high level of ef ectiveness. It has also fueled word of mouth marketing because of the consumer's view of celebrity brands. Street Boba is one of the many celebrity brands in the food and beverage sector. Street Boba experienced various phenomena, ranging from growing rapidly at the beginning of its launch to being weak in competing with non-celebrity brands. Therefore, this study was conducted to further examine celebrity entrepreneurs and EWOM on brand awareness-mediated purchase decision. In addition, there are contradictions in previous research on celebrity entrepreneurs and EWOM on purchase decision as well as brand awareness. The sampling technique in this research is non-probability sampling with accidental sampling method. A total of 113 respondents were obtained through the distribution of online questionnaires. Research respondents are Street Boba consumers who live in the city of Semarang, and have purchased Street Boba products at least once. The data analysis technique used the Structural Equation Modeling (SEM) method through the Analysis Moment of Structural (AMOS) program. The findings of this study indicate that celebrity entrepreneurs and EWOM have a positive and significant ef ect on brand awareness. Furthermore, brand awareness has a positive and significant ef ect on purchase decision. This study also proves that brand awareness can mediate the relationship between celebrity entrepreneurs and EWOM on purchase decision. So it can be concluded that all research hypotheses are accepted and are expected to be an evaluation reference for Street Boba to increase brand awareness and purchase decisions by potential consumers.